Effects of orthodox religious fasting versus combined energy and time restricted eating on body weight, lipid concentrations and glycaemic profile. (2nd January 2021) - Karras, Spyridon N.; Koufakis, Theocharis; Adamidou, Lilian; Antonopoulou, Vasiliki; Karalazou, Paraskevi; Thisiadou, Katerina; Mitrofanova, Elina; Mulrooney, Hilda; Petróczi, Andrea; Zebekakis, Pantelis; Makedou, Kali; Kotsa, Kalliopi
Abstract: For seven weeks, 37 overweight adults followed a hypocaloric diet based on Orthodox Fasting (OF). A hypocaloric, time restricted eating (TRE) plan (eating between 08:00 to 16:00 h, water fasting from 16:00 to 08:00 h) was followed by 23 Body Mass Index (BMI)-matched participants. Anthropometric, glycaemic and inflammation markers and serum lipids were assessed before and after the diets. Both OF and TRE groups demonstrated reductions in BMI (28.54 ± 5.45 vs 27.20 ± 5.10 kg/m 2, p < 0.001 and 26.40 ± 4.11 vs 25.81 ± 3.78 kg/m 2 p = 0.001, respectively). Following the intervention, the OF group presented lower concentrations of total and low-density lipoprotein-cholesterol, compared with the pre-fasting values (178.40 ± 34.14 vs 197.17 ± 34.30 mg/dl, p < 0.001 and 105.89 ± 28.08 vs 122.37 ± 29.70 mg/dl, p < 0.001, respectively). Neither group manifested significant differences in glycaemic and inflammatory parameters. Our findings suggest that OF has superior lipid lowering effects than the TRE pattern.